Sealing of tartaric sulfuric (TSA) anodized AA2024 with nanostructured LDH layers. Issue 17 (3rd February 2016) - Kuznetsov, B.; Serdechnova, M.; Tedim, J.; Starykevich, M.; Kallip, S.; Oliveira, M. P.; Hack, T.; Nixon, S.; Ferreira, M. G. S.; Zheludkevich, M. L.
Abstract : Zn–Al LDH-NO3 was grown on TSA anodized surface of AA2024 aluminum alloy LDH-VO x was obtained from LDH-NO3 via anionic exchange reaction The LDH-VO x layer confers remarkable active corrosion protection. Abstract : In this work, a functional sealing of a TSA anodic layer on AA2024 is suggested based upon the formation of inhibitor-containing Zn–Al layered double hydroxides (LDH). The LDH structures are formed in the pores of the anodic layer and on top of it as a result of hydrothermal treatment in a Zn 2+ -containing bath as shown by the structure, morphology and composition analysis. The resulting LDHs were loaded with a well-known corrosion inhibitor (vanadate). Electrochemical impedance spectroscopy, salt spray tests and scanning vibrating electrode techniques have shown a remarkable improvement in corrosion resistance of the LDH-modified sample in comparison with conventional hot-water sealing. The vanadate-loaded LDHs rendered a significant long-term active protection for the covered aluminum alloy substrate.